2015
DOI: 10.1007/s00253-015-6455-y
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of atopic dermatitis-like skin lesions by IL-4 inhibition of P14 protein isolated from Lactobacillus casei in NC/Nga mice

Abstract: Atopic dermatitis (AD) is a chronic inflammatory skin disease, with a complex etiology encompassing immunologic responses. AD is frequently associated with elevated serum immunoglobulin (Ig) E levels and is exacerbated by a variety of environmental factors, which contribute to its pathogenesis. However, the etiology of AD remains unknown. Recently, reports have documented the role of lactic acid bacteria (LAB) in the treatment and prevention of AD in humans and mice. The LAB, Lactobacillus casei (LC), is frequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Atopic dermatitis is a major allergic disease that results in increased IgE levels and clinically manifests itself as pruritic skin lesions, dermal hyperkeratosis, and hyperplasia ( Abramovits, 2005 ; Silverberg, 2016 ). Recent studies have shown that certain probiotics can play a role in the treatment and prevention of AD ( Kim et al, 2012 , 2015 ). Duolac ATP possesses anti-inflammatory properties in a DNCB-induced AD mouse model ( Kim et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Atopic dermatitis is a major allergic disease that results in increased IgE levels and clinically manifests itself as pruritic skin lesions, dermal hyperkeratosis, and hyperplasia ( Abramovits, 2005 ; Silverberg, 2016 ). Recent studies have shown that certain probiotics can play a role in the treatment and prevention of AD ( Kim et al, 2012 , 2015 ). Duolac ATP possesses anti-inflammatory properties in a DNCB-induced AD mouse model ( Kim et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…During the Japanese cedar pollen season, NC/Nga mice orally administered L. casei Japan Collection of Microorganisms (JCM) 1134T combined with dextran experienced a possible effect on the prevention and treatment of allergic reactions ( Ogawa et al., 2006 ). Furthermore, researchers screened an active ingredient, protein P14, from the L. casei extract, which specifically lowered IgE and IL-4 levels in AD-like NC/Nga mice, suggesting potential therapeutic effects in AD ( Kim et al., 2015b ). Similarly, the administration of L. casei DN–114001 to the diet of children with AD was beneficial to the increase in the count of intestinal flora and its maintenance for five months after the cessation of probiotics ( Klewicka et al., 2011 ).…”
Section: Monostrain Lactobacillus In the Treatment...mentioning
confidence: 99%
“…Similarly, an AD-like in vivo NC/Nga mice model demonstrated that the protein P14, isolated from Lactobacillus casei, can be used as an active immunomodulatory agent for treating patients with AD [74].…”
Section: Microorganism-derived Substancesmentioning
confidence: 99%